The Relationship between Learning Strategies and Learning Style Preferences toward Learners’ Reading Comprehension (Jurnal Sustainable, 2022)
objectives of this research are to find out: (1) the relationship between learning strategies and learning style preferences toward learners’ reading comprehension, (2) the relationship between learning strategies and learners’ reading comprehension and (3) the relationship between learning style preferences and learners’ reading comprehension. This was a correlational research which had been conducted at the twelfth graders of SMKN 6 Bekasi. Isaac and Michael table with 0.05 as the level of significant error was used as the way to determine the number of the sample. From the table, 161 learners became the The sample of this research with the use of simple random sampling as the way to choose the samples. Strategy Inventory of Language Learners (SILL) questionnaires, Perceptual Learning Style Preferences (PLSP) questionnaires and Indonesian National Examination were used as the instruments of this research. All of those instruments were tried out to obtain the valid and reliable items. Then, the data were analyzed using multiple regression. Based on the research result, the research findings were as follows: (1) there is significant relationship between learning strategies and learning style preferences toward learners’ reading comprehension; (2) there is significant relationship between learning strategies and reading comprehension; (3) there is no significant relationship between learning style preferences and reading comprehension. Finally, it can be inferred that (1) the combination of learning strategies and learning style preferences relate with learners’ reading comprehension; (2) learners’ reading comprehension does not significantly depend on learning style preferences but significantly depend on learning strategies.